Using Implementation Science to Evaluate the Implementation of Patient-Reported Outcome Measures (PROMs) in a Clinical Heart Failure Care Setting - Sarah V.C. Lawrason, MSc, PhD; Heather Ross, MSc, MD; Michael McDonald, MD; Juan Duero Posada, MD; Samantha Engbers, BAH; Anne Simard, MHSc (CJC Open)
Background: Patients with heart failure (HF) can experience poor quality of life, recurring hospitalizations, and progressive disease symptoms. Patient-reported outcome measures (PROMs) include patients’ voices in clinical care by assessing patient symptoms, function, and quality of life. In 2022, PROMs were implemented into the electronic health record system (Epic) at a large academic hospital in Toronto, Canada. The purpose of this study was to use implementation science frameworks to systematically evaluate the uptake and integration of PROMs into clinical HF care. Methods: The Reach, Effectiveness, Adoption, Implementation, and Maintenance (RE-AIM) framework guided this mixed-methods, 1-year quality-improvement project. Data sources included clinician use of PROMs, patient-level data on completed PROMs, and semistructured interviews with clinicians. The PROM was the Kansas City Cardiomyopathy Questionnaire-12, which captures 4 domains related to HF: symptom frequency, physical limitations, social limitations, and quality of life. Quantitative data were analyzed using descriptive statistics, and qualitative data were analyzed using behaviour-change frameworks and latent content analysis. Results: Over the course of 1 year, more patients were assigned to PROMs, a higher proportion of patients completed PROMs, and approximately 60% of patients had high questionnaire scores. Clinicians experience barriers related to attention and decision processes, environmental context, and their professional role, in integrating PROMs into practice. Suggested resources include adding language licenses for PROM translations, reducing cognitive load for clinicians assigning and interpreting PROMs in Epic, and champions modelling PROMs in practice. Conclusions: This study demonstrates the benefit of using implementation science frameworks to evaluate the implementation of PROMs in practice and provide actionable recommendations to health systems. Résumé: Contexte: Les patients atteints d’insuffisance cardiaque (IC) peuvent avoir une mauvaise qualité de vie, être hospitalisés à répétition et présenter des symptômes évolutifs de la maladie. Les mesures des résultats de santé rapportés par les patients (PROM) comprennent l’intégration du point de vue des patients dans les soins cliniques par l’évaluation des symptômes, de leur capacité fonctionnelle et de leur qualité de vie. En 2022, les PROM ont été intégrés dans le système de dossiers médicaux électroniques (Epic) d’un grand hôpital universitaire de Toronto, en Ontario, au Canada. L’étude visait à utiliser des cadres de la science de la mise en œuvre pour évaluer systématiquement l’adoption et l’intégration des PROM dans les soins cliniques de l’IC. Méthodologie: Le cadre RE-AIM (Reach, Effectiveness, Adoption, Implementation, and Maintenance) a servi de guide à ce projet d’amélioration de la qualité sur une période d’un an avec des méthodes mixtes. Les sources de données comprenaient les suivantes : utilisation des PROM par les cliniciens; données à l’échelle des patients sur les questionnaires PROM remplis et entrevues semi-structurées avec des cliniciens. Le PROM utilisé était le Kansas City Cardiomyopathy Questionnaire-12, qui englobe 4 domaines liés à l’IC : fréquence des symptômes, contraintes physiques, contraintes sociales et qualité de vie. Les données quantitatives ont été analysées à l’aide de statistiques descriptives; les données qualitatives ont été analysées à partir de cadres de modification de comportement et d’une analyse du contenu latent. Résultats: Sur la période de 1 an, les PROM ont été utilisés chez un nombre croissant de patients, une proportion élevée de patients ont rempli les questionnaires et environ 80 % des patients ont obtenu des scores élevés. Les cliniciens ont rencontré des obstacles (liés à l’attention et au processus décisionnel, au contexte environnemental et à leur rôle professionnel) pour intégrer les PROM dans leur pratique. Les changements proposés pour améliorer l’adoption des PROM comprennent l’ajout de licences en matière de langue pour la traduction des PROM, la réduction du fardeau cognitif pour les cliniciens qui doivent attribuer et interpréter les PROM dans le système Epic et la promotion d’un modèle d’utilisation des PROM dans la pratique. Conclusions: Cette étude démontre l’avantage d’utiliser les cadres de la science de la mise en œuvre pour évaluer l’adoption des PROM dans la pratique et fournir des recommandations concrètes aux systèmes de santé.